ANALISIS PENERAPAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DESA (SILOKDES) DALAM PENGOLAHAN DATA KEUANGAN PADA DESA (Studi Kasus Pada Desa Ngrawan Kec. Berbek Kab. Nganjuk) - Rahmawati, Cinantya Dwi (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to analyze the information system application of the village financial management   and to investigate the problems of Silokdes aplication in Ngrawan Village. This study uses a qualitative research method with a case study approach, while data are collected by interviews and documentation. The  Ministor  of  Home Affairs  regulation No.  113  year  2014  is  used  as  the standard and study framework. The result shows that: (1) Ngrawan Village has used the Silokdes application in administrating and reporting process based on the Ministor of Home Affairs regulation No 113 year 2014, and it has not used the Silokdes application to report the village asset reports and assets granted by the local government. (2) The Ngrawan Village’s problems are the lack of understanding of officials about the accounting process, as well as overwhelming processes  in administrating,  reporting,  and  responsibility process of financial management.Keywords:  village  financial  management,  silokdes  aplication, administrating, reporting, and responsibility, ngrawan Village